Grapevine mono- and sesquiterpenes: Genetics, metabolism, and ecophysiology - Bosman, Robin Nicole; Lashbrooke, Justin Graham (Frontiers in Plant Science, 2023)
Mono- and sesquiterpenes are volatile organic compounds which play crucial roles in human perception of table grape and wine flavour and aroma, and as such their biosynthesis has received significant attention. Here, the biosynthesis of mono- and sesquiterpenes in grapevine is reviewed, with a specific focus on the metabolic pathways which lead to formation of these compounds, and the characterised genetic variation underlying modulation of this metabolism. The bottlenecks for terpene precursor formation in the cytosol and plastid are understood to be the HMG-CoA reductase (HMGR) and 1-deoxy-D-xylylose-5-phosphate synthase (DXS) enzymes, respectively, and lead to the formation of prenyldiphosphate precursors. The functional plasticity of the terpene synthase enzymes which act on the prenyldiphosphate precursors allows for the massive variation in observed terpene product accumulation. This diversity is further enhanced in grapevine by significant duplication of genes coding for structurally diverse terpene synthases. Relatively minor nucleotide variations are sufficient to influence both product and substrate specificity of terpene synthase genes, with these variations impacting cultivar-specific aroma profiles. While the importance of these compounds in terms of grape quality is well documented, they also play several interesting roles in the grapevine’s ecophysiological interaction with its environment. Mono- and sesquiterpenes are involved in attraction of pollinators, agents of seed dispersal and herbivores, defence against fungal infection, promotion of mutualistic rhizobacteria interaction, and are elevated in conditions of high light radiation. The ever-increasing grapevine genome sequence data will potentially allow for future breeders and biotechnologists to tailor the aroma profiles of novel grapevine cultivars through exploitation of the significant genetic variation observed in terpene synthase genes.